THE INFLUENCE OF PACKAGING AND PRICE ON PURCHASING DECISIONS SAPARUA PALM SUGAR IN AMBON CITY MEDIATED BY CUSTOMER SATISFACTION - Silfiena Siahainenia; Rukmuin Wilda Payapo (Jurnal Ekonomi, 2023)
This research aims to examine the influence of packaging and price on purchasing decisions for Saparua palm sugar in the city of Ambon. The population in this study were Ambon city residents who bought and consumed Saparua palm sugar with a sample size of 126 respondents. The research results explain that packaging and price influence purchasing decisions mediated by consumer satisfaction. The advice that can be given is that Saparua palm sugar businesses are more innovative in making representative packaging so that the product can reach a wider market.